Larangan dan Anjuran Dalam Transaksi Menurut Hadits - Lidinirrahman, Muh Saad Said (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Transactions are an essential part of human life and are inseparable from religious values, particularly in Islam. The Hadiths of Prophet Muhammad (peace be upon him), as the second source of Islamic law after the Qur'an, provide ethical and normative guidelines related to economic transactions. This paper discusses prohibitions and recommendations in transactions based on authentic Hadiths. Through a literature study method, this research finds that Islam prohibits practices such as gharar (uncertainty), riba (usury), najasy (fake bidding), fraud, and selling goods not yet possessed. On the other hand, Islam encourages honesty, transparency, justice, and ease in transactions. These principles are highly relevant to the challenges of the modern economy.